Correction of the Hemostatic System During Preventive and Anticipatory Therapy for Multiple Organ Dysfunction - V. V. Golubtsov; I. B. Zabolotsky (Общая реаниматология)
Objective: To determine the specific features of responsiveness of the blood aggregation system (BAS) in relation to the functional state of an organism and to the intensive care regimen in patients with sepsis and posthemorrhage.Materials and methods. A hundred and sixteen patients with massive hemorrhage and 108 with pyoseptic complications were examined. The baseline values of the stable millivolt-range potential were recorded, which were used to correct intensive care. The condition was evaluated by the SAPS II, APACHE III, and MODS scales.Results. The optimization of treatment for multiple organ dysfunction in a subcompensated functional state is to enhance sedation, to eliminate dehydration and vasospasm, to improve rheological blood properties, and to make early membrane detoxification. In a decompensated functional state, the main optimization goals include activation of the central nervous system and elimination of tissue hyperhydration, membrane detoxification with dehydration, inotropic support, activation of the antinociceptive system, prevention of thrombotic events, antibiotic therapy — deescalation.Conclusion. The promptest normalization of BAS creates objective prerequisites for a good outcome; at the same time this leads to the conclusion that correction occurs more rapidly and more effectively in patients receiving the optimized treatment regimen, as evidenced by constant potential recording.